Peritoneal Pseudocyst - A Complication of Lumbo Peritoneal Shunt Surgery - Rajish Sanjit Kumar Shil; Ebrahim Mohammad Khair Al Yousef (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2016)
Placement of a ventriculoperitoneal shunt is an established procedure for treatment of hydrocephalus, however, complications can occur. The most common causes of shunt malfunction are catheter obstruction and infection. The incidence of Ventriculoperitoneal shunt related abdominal complications has been reported to be from 5% to 47% [1]. The most common distal ventriculoperitoneal shunt complications include shunt infection, subcutaneous collection of CSF, peritoneal pseudocyst, bowel perforation, intestinal volvulus, mesenteric pseudotumor, migration of the catheter into the pleural cavity and heart, and development of an incision hernia [2].